Pengembangan Media Pembelajaran Kotak Kartu Misterius (KOKAMI) Berbasis Discovery Learning pada Mata Pelajaran Bahasa Indonesia Kelas V Sekolah Dasar - Safitri, Annisa; Wicaksono, Andri; Zain, M. Yanuardi (Program Studi PGSD, Jurusan Ilmu Pendidikan, STKIP PGRI Bandar Lampung, 2025)
This research is motivated by the lack of interesting and varied learning media in Indonesian language learning. This study aims to develop Kokami (Mysterious Card Box) learning media based on discovery learning in Indonesian language subjects for grade V students of SD Negeri 1 Tanjung Sari. The research method used is R&D with the ADDIE development model consisting of five stages of analysis, planning, development, implementation, and evaluation. Based on the results of the study, media validation was 95%, material expert validation was 88.4%, language expert validation was 88.4% so that the results of the average validation were included in the